Sistem Pendukung Keputusan Pemberian Tunjangan Karyawan Menggunakan Metode Analytical Hierarchy Process (AHP): Studi Kasus: TVRI Nusa Tenggara Timur - Yoman Berchmans; Linus Evrianus Ama Kean; Reynaldo Behar; Yampi R. Kaesmetan (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research aims to address the issues surrounding the allocation of employee benefits at TVRI Nusa Tenggara Timur. Currently, the decision-making process for benefits is solely based on recommendations from supervisors, without taking into consideration employee performance, potentially leading to social jealousy and suboptimal outcomes. In this study, we develop a Decision Support System (DSS) utilizing the Analytical Hierarchy Process (AHP) method to assess employee performance. AHP allows for a hierarchical and objective breakdown of multi-factor problems. The criteria used for evaluation include attendance, behavior, length of service, and dependents. It is expected that the implementation of this DSS will enhance transparency and objectivity in decision-making, minimize employee dissatisfaction, and provide a more robust basis for benefit allocation decisions. This research offers practical contributions to human resource management and decision-making at TVRI Nusa Tenggara Timur.